Evaluation of Thermal Variations of Irrigation on the Osseointegration of Dental Implants: An In vivo Study in Rabbit Models. - Osman Varol; Hakan Akın; Halit Furuncuoğlu; Doğukan Yılmaz (Cumhuriyet University, 2020)
Objectives: Thermal trauma during implant surgery limits the proper healing process. The aim of the study was to investigate the effect of different irrigation temperatures during implant surgery on the osseointegration of dental implants. Materials and Methods: Eight adult male New Zealand white rabbits were used in this study. Total of 32 implants were inserted in each tibia of each rabbit's rear legs. Rabbits were randomly divided according to different irrigation procedures applied (37°C, 24°C, 10°C, and 1°C). Resonance frequency analysis (RFA) was performed following to implant surgery, 1th week, 2nd week, 3rd week, and 1th month. In addition, removal torque values (RTVs) were measured from sacrificed tibias at the end of 30 days. Results: No significant difference in implant stability quotient (ISQ) was detected between groups from the first measurement to 5th measurement. However, there was a statistically significant difference in RTVs between 1°C and 37°C, and 1°C and 10°C (p=0.024 and p=0.013, respectively). Conclusion: Different irrigation temperatures during implant surgery were not effective on the primary and secondary stability values of dental implants in rabbit models.